A metalloproteomics study on the association of mercury with breast milk in samples from lactating women in the Amazon region of Brazil - Santos, Felipe André dos; Cavecci, Bruna [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Franzini, Venessa Pezza [UNESP]; Santos, Ademir dos [UNESP]; Leite, Aline de Lima; Buzalaf, Marilia Afonso Rabelo; Zara, Luiz Fabrício; Padilha, Pedro de Magalhães [UNESP] (Springer Nature, 2015)
This study aimed to identify metalloproteins that lose their metal ions in the presence of mercury (Hg) and bind to Hg in breast milk samples collected from the riverine population of the Madeira River, a tributary of the Amazon River. Initially, total Hg was determined from the hair of lactating women to identify individuals who were contaminated followed by a proteomic analysis of breast milk samples through two-dimensional polyacrylamide gel electrophoresis after acetone precipitation. The presence of Hg in the obtained protein spots was determined by cold vapor atomic absorption spectrometry and cold vapor atomic fluorescence spectrometry. These determinations indicated the presence of Hg in one protein spot, which was then characterized through electrospray ionization tandem mass spectrometry. Based on searches in the UniProt database, this protein spot was identified as lysozyme C.
Keywords: Mercury in breast milk; 2D PAGE; Metalloproteomics study; ESI-MS/MS